Pengaruh Kualitas Pelayanan dan Experiental Marketing Terhadap Kepuasan Pelanggan Pengguna Firstmedia - Suci Pertiwi (Fakultas Bisnis Universitas Mikroskil, 2023)
In the current era of globalization, the internet is not just a secondary need for people in Indonesia, the internet network can facilitate work and entertainment alone. There has been an increase in the number of internet users in Indonesia since the government’s implementation of work-from-home as a preventive measure for the spread of the Covid-19 outbreak. The aim of this research is to find out and analyze the effect of service quality and experiential marketing on customer satisfaction among Firstmedia users. The Type of research used in this research is quantitative research. The sampling technique uses a purposive sampling method and is conducted by distributing questionnaires to 310 samples which are Firstmedia users. The data analysis method used in this research is multiple linear regression. Partial testing (t-test) shows that service quality and experiential marketing variables affect customer satisfaction. Simultaneously (test-F) shows that the variables of service quality and experiential marketing do affect customer satisfaction among Firstmedia Users. The Adjusted R-Square value shows that variables of service quality and experiential marketing can explain variations in customer satisfaction among Firstmedia users 81.3% and the remaining 18.7% is influenced by other variables which are not observed in this research.